Respiratory Microbiome of New-Born Infants - Gallacher, David J.; Kotecha, Sailesh (Frontiers in Pediatrics, 2016)
The respiratory tract, once believed to be sterile, harbors diverse bacterial communities. The role of microorganisms within health and disease is slowly being unraveled. Evidence points to the neonatal period as a critical time for establishing stable bacterial communities and influencing immune responses important for long-term respiratory health. This review summarizes the evidence of early airway and lung bacterial colonization and the role the microbiome has on respiratory health in the short and long term. The challenges of neonatal respiratory microbiome studies and future research directions are also discussed.